PERAN GURU PAI DALAM INTERNALISASI KARAKTER KEPEDULIAN SOSIAL - Nasir, Ulin Nuha; Mustofa, Triono Ali (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This article discusses the concept of social care that is incorporated into the education system in Indonesia through character education. This article highlights the main focus on intellectual aspects of contemporary education, while downplaying the moral and spiritual dimensions. This study examines the correlation between the rapid development of today's era and the decline in a sense of concern among today's adolescents. Teachers are responsible for teaching and improving the moral development of students to encourage effective socialization among students. This research aims to; (1) Describe the role of PAI teachers in internalizing the social care character of students at SMK Batik 1 Surakarta, (2) Describe the form of social care character at SMK Batik 1 Surakarta, (3) Describe the impact of internalizing social care character at SMK Batik 1 Surakarta. This study uses descriptive qualitative research methodology to achieve its goals. The data collection techniques used are interviews, observation, and documentation. This article describes the process of data analysis, which includes collecting data, reducing unnecessary data, presenting data, and drawing conclusions. This study shows the results that the results of this study are; (1) PAI teachers at SMK Batik 1 Surakarta incorporate character education into the Syllabus or RPP, cultivate habits, encourage group work, and encourage mutual assistance among students; (2) Forms of social care carried out at SMK Batik 1 Surakarta, such as infaq, gotong royong, and altruism; (3) This study examines the impact of internalizing the character of social care in SMK Batik 1 Surakarta. The findings revealed two positive outcomes: improved moral and character development of students, and improved interpersonal relationships among students.